STUDI PENGARUH pH AWAL MEDIA DAN KONSENTRASI SUBSTRAT PADA PROSES FERMENTASI PRODUKSI BIOETANOL DARI HIDROLISAT TEPUNG BIJI KLUWIH (Actinocarpus communis) DENGAN MENGGUNAKAN Saccharomyces cerevisiae - Wikrama Yuda, I Gede Yogi; Mahaputra Wijaya, I Made; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 2 (2018): AprilDO - 10.24843/JRMA.2018.v06.i02.p03, 2018)
The aims of this study were to determine the optimum pH of media and substrate concentration on fermentation process that affected the production of bioetanol from kluwih ( Actinocarpus communis ) seed by  Saccharomyces cerevisiae , and to obtain initial pH of media and substrate concentration on fermentation process that can a obtain the highest concentration of bioethanol. The research was designed by 2 factors. The first factor is initial pH of media that consist of three levels: 4, 4.5, and 5. The second factor is substrate concentration that consist of three levels: 2.5 %, 5 %, and 7.5 %. The data was obtained from series of tests and then it analyzed and produced presented by descriptive method. The results showed that the initial pH of media had an effect on ethanol content, and the pH, but not effected on total resulting suspended solid. Substrate concentration had an effect on ethanol content and total suspended solid. Interaction of both treatments had an effect on ethanol content from fermented flour of kluwih seed by used  Saccharomyces cerevisiae . The best treatment to produce ethanol from fermented flour of  kluwih seed is by using the initial pH of media 4.5 and substrate concentration amount 7.5 % that yielded the highest ethanol content of 6.13 mL.                                                                                                                                           Key words:    Actinocarpus communis , ethanol, fermentation, the initial pH of media, substrate concentration